Monocytes in acute myocardial infarction - Ruparelia, N (2013)
Acute myocardial infarction (AMI) results in the activation of the innate immune system with monocytes playing critical roles in both the initial inflammation following myocardial ischaemia and subsequent recovery. Monocytes are a heterogeneous cell population and observations from experimental models demonstrate that immediately following myocardial injury, classical inflammatory monocytes, which are highly phagocytic, are recruited to ischaemic myocardium from the bone marrow and spleen and peak at 48 hours. This is followed by the recruitment of non-classical monocytes that are involved in repair and healing, peaking at day 5. The monocyte response in humans following AMI is currently poorly understood. Due to their central role in the pathogenesis of AMI, monocytes are attractive both as potential biomarkers to inform of extent of myocardial injury (and recovery) and also as therapeutic targets with the specific targeting of monocytes in experimental models resulting in reduced infarction size and improved LV remodelling. However, in spite of these promising results and our greater understanding of the pathogenesis of AMI, no immune-modulating therapeutic has been translated into routine clinical practice. We therefore hypothesized that characterisation of the monocyte response to AMI by flow cytometry and gene expression profiling in both experimental models and humans would give novel insights into underlying biological processes and function (both locally in the myocardium and systemically), identify novel therapeutic targets, enable their use as cellular biomarkers of disease, and test conservation between species validating the experimental model for future investigation. Classical inflammatory monocytes were found to significantly increase in the peripheral blood 48 hours following AMI in both mice and humans, with the magnitude of the monocyte response correlating with the extent of myocardial injury in both species. Gene expression profiling of peripheral circulating monocytes following AMI identified a number of candidate genes, biological pathways and upstream regulators that were conserved between species and that could represent novel therapeutic targets. Furthermore, in an experimental model of AMI, leukocytes appeared to have effects beyond the ischaemic myocardium, with leukocyte recruitment in remote myocardium and in kidneys associated with elevated inflammatory markers and endothelial activation.